1999
DOI: 10.1159/000054457
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Prolactin Secretion following Lactotrope Escape from Dopamine Action

Abstract: Modulation of Ca2+ channels has been shown to alter cellular functions. It can play an important role in the amplification of signals in the endocrine system, including the pleiotropically regulated pituitary lactotropes. Prolactin (PRL) secretion is tonically inhibited by dopamine (DA), the escape from which triggers acute episodes of hormone secretion. The magnitude of these episodes is explained by a potentiation of the PRL-releasing action of secretagogues such as thyrotropin-releasing hormone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 82 publications
0
3
0
1
Order By: Relevance
“…Even though the molecular bases for the stimulation of Ca 2+ currents remain to be fully determined, these channels appear to be a major control point in the regulation of hormone secretion, and could be responsible for the DA-escape facilitation of secretagogue-induced PRL secretion. From the results in this and the companion paper [44], we propose that the escape from the tonic DA action recruits voltage-dependent Ca 2+ channels. Consequently, after DA washout, a greater number of HVA, L-type Ca 2+ channels are available to conduct Ca 2+ in response to a TRH-induced depolarization.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Even though the molecular bases for the stimulation of Ca 2+ currents remain to be fully determined, these channels appear to be a major control point in the regulation of hormone secretion, and could be responsible for the DA-escape facilitation of secretagogue-induced PRL secretion. From the results in this and the companion paper [44], we propose that the escape from the tonic DA action recruits voltage-dependent Ca 2+ channels. Consequently, after DA washout, a greater number of HVA, L-type Ca 2+ channels are available to conduct Ca 2+ in response to a TRH-induced depolarization.…”
Section: Discussionmentioning
confidence: 56%
“…Phosphorylation of α1 and β subunits of voltage-dependent calcium channels by protein kinases A and C [40, 41]is known to enhance their opening probability, leading to a larger Ca 2+ influx into the cell during the open state [42, 43]. Along this line, we have recently observed that DA withdrawal increases the rate of phosphorylation of the α1 subunit of voltage-dependent calcium channels in cultured pituitary lactotropes and GH 4 C 1 /D 2 -DAR cells, within a time frame that also parallels the rapid increase in Ca 2+ conductance [44]. …”
Section: Discussionmentioning
confidence: 99%
“…currents in diverse human tissues and cell lines: heart, neuroblastoma, T-cells, and endocrine cells (5)(6)(7)(8)(9)(10). Dual modulation by PKC is often observed with activation followed by, or concomitant with, inhibition (5,10).…”
mentioning
confidence: 99%
“…100 Más aún, el sistema dopaminérgico hipotalámico tiene una actividad reducida en un modelo de rata autista, 101 que permite explicar las modificaciones en la concentración de prolactina sistémica de niños primordialmente medicados. 102,103 Cerebelo. El cerebelo es una estructura que muestra una alteración significativa en las personas con autismo (Fig.…”
Section: Circunferencia De La Cabeza Y Volumenunclassified